Embodied time travel in VR: from witnessing climate change to action for prevention - Pi, Yuke; Pan, Xueni; Slater, Mel; Świdrak, Justyna (Frontiers in Virtual Reality, 2025)
This study explores the impact of embodied experiences in Virtual Reality (VR) on individuals' attitudes and behavior towards climate change. A total of 41 participants were divided into two groups: an embodied group that interacted with a virtual environment through full-body avatars, and a non-embodied group that observed the scenarios from an invisible observer's point of view. The VR experience simulated the progressive consequences of climate change across three generations within a family, aiming to make the abstract and relatively distant concept of climate change a tangible and personal issue. The final scene presented an optimistic scenario of a future where humans had successfully combated climate change through collective action. The evidence suggests that there is an effect of the scenario on the carbon footprint response, even 6 weeks after the VR exposure, irrespective of condition. Additionally, increases were found in participants' perceived influence on climate action and engagement in pro-environmental behaviors, with the embodied group showing a more pronounced response in the short term. These findings suggest that immersive VR experiences that incorporate virtual embodiment can be an effective tool in enhancing awareness and motivating pro-environmental behavior by providing a powerful and personal perspective on the impacts of climate change.